2022
DOI: 10.1177/11795476221088472
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Post COVID19 Giant Cell Arteritis and Polymyalgia Rheumatica With Visual Loss

Abstract: COVID-19 shares some features of giant-cell arteritis, in which the diagnosis needs a high suspicion for prompt investigation and therapy. When the diseases coexist this might lead to diagnosis delay with grave consequences. We reported a case of a post-COVID-19 giant cell arteritis and polymyalgia rheumatica with visual loss. We treated the patient with pulse methylprednisolone 1 gm daily for 3 consecutive days followed by 60 mg prednisolone for 4 weeks until normalization of ESR, and then, gradual withdrawal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several cases of GCA in SARS-CoV-2 infected patients have been described ( Table 1 ). COVID-19 is known for its immune dysregulation and a strong association between interleukins and rheumatic diseases was found during the COVID-19 pandemic: 3 for example, IL-6 and IL-17 showed association between polymyalgia rheumatica (PMR) and arthritis among COVID-19 patients. 4 Oda et al reported a case of adult large vessel vasculitis after SARS-CoV-2 infection 5 and hypothesised, after a previous report on endothelial cell infection and endotheliitis in patients with COVID-19, 6 that this infection and endotheliitis could have led to vasculitis.…”
mentioning
confidence: 99%
“…Several cases of GCA in SARS-CoV-2 infected patients have been described ( Table 1 ). COVID-19 is known for its immune dysregulation and a strong association between interleukins and rheumatic diseases was found during the COVID-19 pandemic: 3 for example, IL-6 and IL-17 showed association between polymyalgia rheumatica (PMR) and arthritis among COVID-19 patients. 4 Oda et al reported a case of adult large vessel vasculitis after SARS-CoV-2 infection 5 and hypothesised, after a previous report on endothelial cell infection and endotheliitis in patients with COVID-19, 6 that this infection and endotheliitis could have led to vasculitis.…”
mentioning
confidence: 99%
“…There have been various case reports in the literature regarding immune-mediated flare-ups of inflammatory disease or new-onset inflammatory disease following COVID-19 infection or administration of SARS-COV-2 vaccines. For example, one case report discussed a patient that presented with bilateral shoulder and hip stiffness, vision loss, and jaw claudication about a month following COVID-19 infection [ 9 ]. This patient had a temporal artery biopsy done which showed recanalization after inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had a temporal artery biopsy done which showed recanalization after inflammation. However, other imaging, such as computed tomography angiography (CTA) and magnetic resonance angiography (MRA), were negative for aortitis [ 9 ]. Another case discussed a patient that tested positive for COVID-19 infection and initially presented with bilateral temporal artery tenderness and headaches along with cough and fever, which was thought to be related to COVID-19 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the controversy about whether this binding of the spike protein can lead to direct viral infection of the endothelial cells, the binding can eventually result in the dysfunction of the endothelial cells through damage. Furthermore, a suggestion has been made that SARS-CoV-2 infection can also induce giant cell arteritis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%